2018
DOI: 10.1371/journal.pone.0199361
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibody reagents for characterization of drug- and tumor microenvironment-induced changes in epithelial-mesenchymal transition and cancer stem cells

Abstract: The presence of cancer stem cells (CSCs) and the induction of epithelial-to-mesenchymal transition (EMT) in tumors are associated with tumor aggressiveness, metastasis, drug resistance, and poor prognosis, necessitating the development of reagents for unambiguous detection of CSC- and EMT-associated proteins in tumor specimens. To this end, we generated novel antibodies to EMT- and CSC-associated proteins, including Goosecoid, Sox9, Slug, Snail, and CD133. Importantly, unlike several widely used antibodies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…#AF1997; R&D Systems). CSC multiplex IFA consisting of CD133, CD44v6, and NANOG (panel B) was performed using unconjugated rabbit monoclonal CD133 (47-10) antibody developed by our group (25), mouse monoclonal anti-CD44v6 antibody, and goat polyclonal antibody to human NANOG (AF1997). For both panels, 10 mg/mL of donkey antirabbit-AF647, anti-mouse-AF488, and anti-goat-AF555 (all from Life Technologies) were used as secondary antibodies.…”
Section: Csc Immunofluorescence Assaymentioning
confidence: 99%
“…#AF1997; R&D Systems). CSC multiplex IFA consisting of CD133, CD44v6, and NANOG (panel B) was performed using unconjugated rabbit monoclonal CD133 (47-10) antibody developed by our group (25), mouse monoclonal anti-CD44v6 antibody, and goat polyclonal antibody to human NANOG (AF1997). For both panels, 10 mg/mL of donkey antirabbit-AF647, anti-mouse-AF488, and anti-goat-AF555 (all from Life Technologies) were used as secondary antibodies.…”
Section: Csc Immunofluorescence Assaymentioning
confidence: 99%
“…NSCLC cells with CSC characteristics are enriched within populations with specific cell markers such as CD44, CD166, ALDH1A1, Sox2, Oct4, Nanog, and CD133, which also contribute directly to the CSC properties. These markers may be associated with carcinogenesis and tumor progression, and may also play an important role in maintaining the stemness phenotype of CSCs [811]. Therefore, studies on CSCs and a better understanding of CSC biology in lung cancer will provide a basis for developing novel diagnostic and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…23 In terms of its functions, EMT plays a vital role in modulating embryonic development, wound healing, cancer cell metastasis, and drug resistance. [24][25][26][27] It is worth noting that in non-small cell lung cancer (NSCLC), UBE2T enhances the degradation of FOXO1 in a ubiquitination-dependent manner, thus repressing EMT of NSCLC cells. 28 Similarly, this study found that FAST1 up-regulation led to up-regulated N-cadherin and Snail but inhibited E-cadherin and…”
Section: Discussionmentioning
confidence: 99%